Nivel de calidad de cuidados y su relación con el nivel de conocimientos y funcionamiento familiar del cuidador familiar de pacientes con cáncer de colon colostomizados - Ulloa Barbarán, Yesenia (2015)
This descriptive correlational research study was conducted in order to determine the relationship between the quality level of care with the level of knowledge and family functioning of family caregivers of adult patients with colon cancer colostomy; attending the Hospital Victor Lazarte Echegaray. The sample universe consisted of 20 families of patients diagnosed with colon cancer treated at the Oncology Unit. Test to assess the level of Quality of Care, Level of Knowledge and the Family Caregiver Operation: For data collection 3 instruments were applied. According to the results it came to the following conclusions: Tier Quality Care for Family Caregivers of Patients with Colon Cancer colostomy is Regular (60%), the level of knowledge is Medium (50%) and the level Functional Family Functioning is moderately (75%). We found that there is a statistically significant relationship between the variables Care Quality Level and Level of Knowledge and variables Care Quality Level and Level of Family Functionality.